TEKNIK ARGUMENTASI HUSEIN JA’FAR AL-HADAR DALAM DISKUSI KETAATAN PADA ORANG TUA BERSAMA TRETAN MUSLIM - Soufi Wiranti; Mawehda (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2021)
Argumentation is one of the best techniques in conveying da’wah messages, the prophets and even Allah SWT in conveying His Word use many argumentation techniques either through comparison, contradiction, equality, cause and effect, genus and definition, circumstances or circumstances and testimony or authority. The superiority of the argumentation technique used as a way of delivering da’wah messages can influence mad’u beliefs to agree, believe, and want to follow the will of the da’i. In addition, through arguing the truth of Islam is more accountable and shows the da’i has the breadth of Islamic knowledge. The purpose of this paper is to find out the elements, techniques and patterns of argumentation of Husein Ja’far Al-Hadar in the discussion of Obedience to Parents with Tretan Muslim. This study uses a qualitative approach through a theoretical review of argumentation. The results of this study show that the elements, techniques and patterns according to Gorys Keraf and Toulmin are: a) The argumentation elements used by Habib Ja’far consist of claims, datum, and warrant, while the elements of backing, modal qualifier and rebuttal are not widely used. b) The argumentation techniques used by Habib Ja’far include genus and definition techniques, comparison techniques, equation techniques, causal techniques, and witness and authority techniques. c) The argument pattern used by Habib Ja’far dominantly uses the 3rd model which has an element structure of claims, datum, and warrant